Neurohype and the Law: A Cautionary Tale - Morse, Stephen J. (2019)
This chapter suggests that for conceptual, empirical, and practical reasons, neuroscience in general and non-invasive brain imaging in particular are not likely to revolutionize the law and our conception of ourselves, but may make modest contributions to legal policy and case adjudication if the legal relevance of the science is properly understood